2019
DOI: 10.31616/asj.2019.0033
|View full text |Cite
|
Sign up to set email alerts
|

Learning Curve for Robot-Assisted Percutaneous Pedicle Screw Placement in Thoracolumbar Surgery

Abstract: Study DesignRetrospective review of an initial cohort of consecutive patients undergoing robot-assisted pedicle screw placement.PurposeWe aimed to evaluate the learning curve, if any, of this new technology over the course of our experience.Overview of LiteraturePercutaneous pedicle screws have specific advantages over open freehand screws. However, they require intraoperative imaging for their placement (e.g., fluoroscopy and navigation) and require increased surgeon training and skill with the learning curve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 25 publications
0
41
2
Order By: Relevance
“…Each surgeon's learning curve of percutaneous minimally invasive puncture technology and robot‐assisted puncture might have affected the experimental data 17–19 ,. 22–26 The longest follow‐up time was 3 months after the surgery in this study. Hence, longer follow‐up time was needed to explore the factors influencing the results.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Each surgeon's learning curve of percutaneous minimally invasive puncture technology and robot‐assisted puncture might have affected the experimental data 17–19 ,. 22–26 The longest follow‐up time was 3 months after the surgery in this study. Hence, longer follow‐up time was needed to explore the factors influencing the results.…”
Section: Discussionmentioning
confidence: 81%
“… 24 The surgeon should understand the characteristics of the robot system and master its operation process, including learning to effectively integrate the robot operating system into the entire surgical process. Previous studies have reported 25 , 26 that the learning curve of robot‐assisted puncture screw insertion is in the range of 20–50 surgeries. At least 25 surgeries must be completed to acquire proficiency in this technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that the surgical outcomes from the initial experience to practiced experience showed no remarkable difference. [27,28] Thus, surgical skills are relatively less demanding, thereby indicating that RA technique may prevent malposition by reducing unnecessary manual mistakes. Fifth, due to the precise insertion of RA technique, the rate of medial penetrations was greatly reduced, avoiding the relevant severe complications, such as spinal cord and nerve root injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown little difference between novice and experienced surgeons with respect to procedural efficiency in placing robotically guided pedicle screws; despite this, a trend towards increasing efficiency after the performance of a certain number of cases or placement of a certain number of screws placed has been reported (45,46). The only study in a full navigation enabled robotic platform that comments on learning curve showed no difference between the attending and the first participating fellow.…”
Section: Learning Curvementioning
confidence: 99%